2018
DOI: 10.1021/acsami.8b07981
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Fabrication of Nanostructured Tin Oxide Anodes for High-Energy Lithium-Ion Batteries

Abstract: Although tin and tin oxides have been considered very promising anode materials for future high-energy lithium-ion batteries due to high theoretical capacity and low cost, the development of commercial anodes falls short of expectations. This is due to several challenging issues related to a massive volume expansion during operation. Nanostructured electrodes can accommodate the volume expansion but typically suffer from cumbersome synthesis routes and associated problems regarding scalability and cost efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 71 publications
0
9
0
Order By: Relevance
“…In a similar manner, issues posed by commercial LIB binders (i.e., polyvinylidene flouride, PVDF) in electrode fabrication can be addressed with a substitution for other binder molecules or multifunctional binders, however, under fabrication and electrochemical testing conditions, it does not eliminate side reactions or possible delamination from the current collector. The majority of LIB electrode fabrication without the use of binders utilizes nanostructures , most often synthesized on carbon/2D material supports , or via electrospraying techniques. ,, The nanostructures again face scalability issues and the electrospraying techniques use harmful solvents to create the precursor dispersion. Although previous investigations have advanced the fabrication methodology, they have yet to pair solvent- and binder-free bulk electrode fabrication for LIB systems.…”
mentioning
confidence: 99%
“…In a similar manner, issues posed by commercial LIB binders (i.e., polyvinylidene flouride, PVDF) in electrode fabrication can be addressed with a substitution for other binder molecules or multifunctional binders, however, under fabrication and electrochemical testing conditions, it does not eliminate side reactions or possible delamination from the current collector. The majority of LIB electrode fabrication without the use of binders utilizes nanostructures , most often synthesized on carbon/2D material supports , or via electrospraying techniques. ,, The nanostructures again face scalability issues and the electrospraying techniques use harmful solvents to create the precursor dispersion. Although previous investigations have advanced the fabrication methodology, they have yet to pair solvent- and binder-free bulk electrode fabrication for LIB systems.…”
mentioning
confidence: 99%
“…The use of lithium-ion batteries is rapidly increasing due to wide applications in portable electronic devices. Development of batteries with higher energy density, superior power density, excellent cycle life, and minimum aging effect of the electrodes is crucial to meet the increasing energy supply requirements for futuristic applications. Presently, graphite is used as the anode but can no longer meet the ever-increasing demand for the higher electrochemical performance of lithium-ion batteries due to its lower energy density. In order to circumvent this issue, several metal oxides such as nano SnO 2 , Fe 3 O 4 , Mn 3 O 4 , and so forth have been investigated as these materials have superior lithium storage properties. However, these metal oxides upon reduction form alloys with lithium (Li x M) and Li 2 O inside the half-cell. Second, these kinds of anodes undergo severe volume variation due to continuous lithium intercalation/deintercalation processes, which ultimately leads to electrode pulverization. These physical processes ultimately result in lowering of the capacity after few cycles and poor cycling stability.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, anodically generated nanostructured tin oxide (SnO x ) layers have received great scientific interest due to their encouraging electrochemical, optical, and semiconducting properties, which make them promising alternatives for a broad range of applications, including photoelectrochemical water splitting [1], photocatalysis [2], photovoltaics [3], energy storage systems [4,5], gas sensors [6], and others [7]. Numerous studies have indicated that these superior properties are partially a result of the nanostructured morphology of the oxide films.…”
Section: Introductionmentioning
confidence: 99%